A computer simulation technique to estimate die load and energy during sinter-forging process - Jha A.K.; Singh S.; Kumar S. (My University, 2025)
This paper presents a computer simulation of sinter-forging process under axi-symmetric deforming condition. The simulation model is based on the mathematical analysis published earlier. During the analysis of sinter-forging process by equilibrium method, an appropriate interfacial friction law, yield criterion for porous material and inertial forces have been considered in addition to barreling. Close agreement is reached between the previously reported experimental and theoretical results and it is concluded that the simulation technique is appropriate for predicting the deformation load and energy during axi-symmetric sinter-forging process.